2022
DOI: 10.3390/ani12050637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Competitive ELISA-Positive Results of Piroplasmosis on the Performance of Endurance Horses

Abstract: Endurance is an increasingly popular equestrian sport. However, in southern Europe, there is a high prevalence of horses that are asymptomatic carriers of equine piroplasmosis (EP), a tick-borne disease that could affect their performance. This study aimed to evaluate the impact and influence of EP on the performance of endurance horses. Blood samples were collected from 40 horses in Extremadura, Spain, before and after a race, in different national elite horse endurance competitions. Hematological and biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In another study, LDH and AST contents in the same horses exercised in May and September were measured and it was reported that LDH and AST contents increased after exercise (Kedzierski et al, 2009). In addition, it was found that LDH and AST contents increased after exercise in horses with piroplasmosis (Bravo-Barriga et al, 2022). In a two-race study on endurance horses, it was reported that AST and ALT contents increased substantially in both races compared to the pre-race period (Larsson et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…In another study, LDH and AST contents in the same horses exercised in May and September were measured and it was reported that LDH and AST contents increased after exercise (Kedzierski et al, 2009). In addition, it was found that LDH and AST contents increased after exercise in horses with piroplasmosis (Bravo-Barriga et al, 2022). In a two-race study on endurance horses, it was reported that AST and ALT contents increased substantially in both races compared to the pre-race period (Larsson et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…Studies on Thoroughbred racehorses reported increased LDH, AST and ALT after exercise (Allaam et al., 2014 ). Horses with piroplasmosis have shown similar increases in LDH and AST due to exercise (Bravo‐Barriga et al., 2022 ). In endurance horses, a significant hike in AST and ALT levels was found after a race compared to pre‐race measurements (Larsson et al., 2013 ).…”
Section: Discussionmentioning
confidence: 98%
“…This results in an elevated heart rate, higher blood pressure, the release of catecholamines (adrenaline and noradrenaline), and a slowed-down gastrointestinal process. The activation of this axis leads to an instantaneous reaction to stress (Brown, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Europe have shown a wide range of seroprevalence rates for equine piroplasmosis: T. equi seroprevalence ranged from 1% in the Netherlands to 58% in France, with an estimated overall seroprevalence of 30.0% [12,[32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 98%